Rare Association of Takayasu Arteritis and Antiphospholipid Syndrome with Severe Thrombocytopenia - Datta, Abhijit; Sharma, Prayush; Ahmed, Shamim; Haq, Syed Atiqul (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
The association of Takayasu arteritis (TA) with antiphospholipid syndrome (APS) has rarely been described in the literature. This paper reports the first documented case of TA and APS in a 24-year-old woman in Bangladesh. This patient had claudication pain in upper and lower limbs for four years and Raynaud’s phenomenon in right hand for eight months. During the course of her illness, she suddenly developed deep vein thrombosis in left superficial femoral, popliteal and posterior tibial veins. Conventional angiography revealed total occlusion of right subclavian artery and 60-70% stenosis of right common iliac artery. CT angiography of right upper limb also supported these findings along with increased wall thickening in the 2nd part of right subclavian artery and moderate narrowing of the 1st part of right axillary artery. She had persistently positive anticardiolipin antibodies in high titers, positive lupus anticoagulant (LA), prolonged activated partial thromboplastin time (APTT) and severe thrombocytopenia. We started high dose prednisolone (1mg/kg daily). Her platelet count increased rapidly. Based on review of 10 case reports, we considered the rare association of TA and APS. Both conditions should be determined promptly for the sake of early institution of the appropriate therapy. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 59-63